Effect of Zinc Containing Fertilizers in Organic and Inorganic Forms on the Yield of Barley Crop and Uptake of Nutrients - AKAY, AYSEN; KAYA, MUSTAFA HARMAN (Asian Journal of Chemistry, 2010)
This study was conducted to investigate the effect of treatment of the barley crop (Karatay-94) with zinc ontaining fertilizer under field conditions on two locations. The study was designed according to a randomised complete block experimental design in three replicates and at five different sources of zinc (Zn-gluconate, Zn-pyruvate, ZnO, ZnSO4, Zn-EDTA) and were applied on the leaf in three different doses (0-0.75-1.50 kg/da Zn). The highest grain yield in the study was obtained from ZnO, ZnSO4 and Zn-pyruvate applications on both locations. Although significant increases occurred in yield when zinc sources were applied in different doses on the first location (P < 0.05), no statistical differences were observed among zinc sources. On both locations in the study, significant differences were observed in regard to phosphorus and zinc contents of the flag leaf, zinc content in the grain and zinc taken up by the grain. Since no statistical differences were observed among zinc sources on both locations (P < 0.05), a dose of 0.75 kg Zn/da of ZnSO4 can be recommended due to its economic criteria.